(untitled) (Malaysian Management Journal, 2024)
The palm oil industry in Malaysia has faced issues of lower palm oil price and limited land area, and these issues have created a challenging environment for plantation companies to operate in. Plantation companies are constrained in maximizing their profits. Thus, this paper aims to examine the Economic Value Added (EVA) and the factors that influence the EVA of different value chain activities. The dynamic generalized method of moments (DGMM) estimators were adopted for the analysis and the focus was on the -40 Malaysian plantation companies that were listed in the Bursa Malaysia from 2010 to 2018. The results revealed that both downstream integrated activities, namely oleo-chemicals/biodiesel and refineries activities had a significant influence on the plantation companies’ EVA, with the coefficient value 1.12 and 0.09 respectively. Other factors such as the gross margin, crude palm oil price, and exchange rate also significantly influenced the plantation companies’ EVA. The empirical results which were based on the plantation companies’ EVA were influenced by different value chain activities as expected. The findings show that the downstream integrated activities like refineries, and oleo-chemicals/biodiesel activities have played a significant role in increasing the EVA of plantation companies.